Molecular Approaches to the Treatment, Prophylaxis, and Diagnosis of Alzheimer's Disease: Endoplasmic Reticulum Stress and Immunological Stress in Pathogenesis of Alzheimer's Disease - Toru Hosoi; Koichiro Ozawa (Elsevier, 2012)
Alzheimer's disease (AD) is an age-related neurodegenerative disorder, accompanied by neuronal loss and the formation of senile plaques in the brain. Glial cells, such as microglia, have been shown to be activated and induce chronic inflammatory responses in AD brain. The endoplasmic reticulum (ER) functions to facilitate protein folding. However, ER stress occurs when cells are exposed to stress. Mounting evidence suggests that ER stress is involved in the pathology of AD. Meanwhile, recent findings suggested crosstalk between ER stress and immune function. However, the mechanisms linking the progression of AD with ER and immunological stress are still not clear. In the present paper, we review and discuss recent results regarding the mechanism of AD pathogenesis, focusing on ER stress and immunological stress. Keywords:: endoplasmic reticulum stress, inflammation, glial cell, neuron, Alzheimer's disease